Globalizing Production Structure and Intra-Industry Trade: The Case of Turkey - Kılavuz, Emine; Erkekoglu, Hatice; Topcu, Betul Altay (International Journal of Economics and Financial Issues, 2013)
Globalization and increased competition have forced countries to pursue more competitive policies. Today's commodities are not homogeneous and also they cannot be produced in a single country or region. it is essential for countries to focus on products which have high added value or to optimize their natural resources in the most effective areas. In this study, intra-industry trade rates were calculated for sectors which constitute 60% of Turkey's overall export volume for the 1990–2011 period. Furthermore, vertical and horizontal intra-industry trade rates were measured and compared with Turkey’s trading partners. It was concluded that the best-exporting sectors did not appear to have high intra-industry trade values and they tended to provide lower quality products into the global production process. In other words, Turkey is the part of the global production process within the framework of comparative advantage based on factor endowments. Keywords: Turkey; Global Production Process; Horizontal and Vertical Intra-Industry Trade; High and Low Quality Intra-Industry Trade JEL Classifications: F13; F14